2020
DOI: 10.1038/s41598-020-71289-z
|View full text |Cite
|
Sign up to set email alerts
|

Donor myeloid derived suppressor cells (MDSCs) prolong allogeneic cardiac graft survival through programming of recipient myeloid cells in vivo

Abstract: Solid organ transplantation is a lifesaving therapy for patients with end-organ disease. Current immunosuppression protocols are not designed to target antigen-specific alloimmunity and are uncapable of preventing chronic allograft injury. As myeloid-derived suppressor cells (MDSCs) are potent immunoregulatory cells, we tested whether donor-derived MDSCs can protect heart transplant allografts in an antigen-specific manner. C57BL/6 (H2K b , I-A b) recipients pre-treated with BALB/c MDSCs were transplanted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated the ability of MDSCs to prolong cardiac graft survival in a murine model, which was significantly reduced when MDSCs were depleted (45,46), and M-MDSCs were shown to promote organ acceptance through recruitment of regulatory T cells in clinical kidney transplantation (47). Furthermore, studies in islet and heart transplantation have demonstrated an association between MerTK function and M-MDSC mediated transplant tolerance, namely through their ability to recruit regulatory T cells (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the ability of MDSCs to prolong cardiac graft survival in a murine model, which was significantly reduced when MDSCs were depleted (45,46), and M-MDSCs were shown to promote organ acceptance through recruitment of regulatory T cells in clinical kidney transplantation (47). Furthermore, studies in islet and heart transplantation have demonstrated an association between MerTK function and M-MDSC mediated transplant tolerance, namely through their ability to recruit regulatory T cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the inflammatory microenvironment, these cells are capable of mediating immunosuppression through secretion of anti-inflammatory cytokines, recruitment of regulatory immune cells, exhaustion of pro-inflammatory cells through nutrient sequestering, and facilitating cell polarization to anti-inflammatory phenotypes (14). Previous studies have demonstrated the ability of MDSCs to prolong cardiac graft survival in a murine model, which was significantly reduced when MDSCs were depleted (45, 46), and M-MDSCs were shown to promote organ acceptance through recruitment of regulatory T cells in clinical kidney transplantation (47). Furthermore, studies in islet and heart transplantation have demonstrated an association between MerTK function and M-MDSC mediated transplant tolerance, namely through their ability to recruit regulatory T cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the presence of donor MDSCs promoted allograft acceptance as all the engrafted patients and all HDMC timepoints had them. Although it could be presumed that the high chimerism status at these time points account for their donor derived origin but a recent murine study revealed that donor MDSCs promote cardiac allograft tolerance via induction of recipient derived MDSCs ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ling Zhou, et al found a cardioprotective role of MDSCs in heart failure [73] although the human MDSC response in heart transplantation remains unstudied. In murine models, several studies demonstrated MDSC were required for the induction of transplantation tolerance [47,74,75]. Some authors reported the development of MDSC and induction of tolerance after treating recipients with rapamycin and costimulatory blockade with anti-CD40L mAb [76,77] in contrast to mice treated with either rapamycin or anti-CD40L mAb alone [77].…”
Section: Heart Corneal Pancreatic Islets and Skin Transplantationmentioning
confidence: 99%